2021
DOI: 10.4171/lem/1001
|View full text |Cite
|
Sign up to set email alerts
|

Rationality of complete intersections of two quadrics over nonclosed fields

Abstract: We study rationality problems for smooth complete intersections of two quadrics.We focus on the three-dimensional case, with a view toward understanding the invariants governing the rationality of a geometrically rational threefold over a nonclosed field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
6
0
2
Order By: Relevance
“…The IJT obstruction has been used to great effect to study rationality of geometrically rational threefolds over non-closed fields: Hassett-Tschinkel (over R) [HT21b] and Benoist-Wittenberg (over arbitrary fields) [BW] showed this obstruction characterizes rationality for smooth complete intersections of two quadrics in P 5 , and Kuznetsov-Prokhorov used it for several cases of their classification of rationality for prime Fano threefolds [KP]. However, Benoist-Wittenberg also showed that the IJT obstruction is not sufficient to characterize rationality by constructing an example of a (non geometrically standard) real conic bundle threefold X → S whose intermediate Jacobian is trivial but such that S(R) is disconnected; hence, the IJT obstruction vanishes but X has a Brauer obstruction to (stable) rationality over R [BW20, Theorem 5.7].…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations
“…The IJT obstruction has been used to great effect to study rationality of geometrically rational threefolds over non-closed fields: Hassett-Tschinkel (over R) [HT21b] and Benoist-Wittenberg (over arbitrary fields) [BW] showed this obstruction characterizes rationality for smooth complete intersections of two quadrics in P 5 , and Kuznetsov-Prokhorov used it for several cases of their classification of rationality for prime Fano threefolds [KP]. However, Benoist-Wittenberg also showed that the IJT obstruction is not sufficient to characterize rationality by constructing an example of a (non geometrically standard) real conic bundle threefold X → S whose intermediate Jacobian is trivial but such that S(R) is disconnected; hence, the IJT obstruction vanishes but X has a Brauer obstruction to (stable) rationality over R [BW20, Theorem 5.7].…”
Section: 3mentioning
confidence: 99%
“…In the one oval example [FJS + , Theorem 1.3(2)] Y (R) = ∅ is connected, and irrationality is shown using the intermediate Jacobian torsor (IJT) obstruction. This obstruction to rationality is a refinement over non-closed fields of the intermediate Jacobian obstruction of Clemens-Griffiths [CG72], and was recently introduced by Hassett-Tschinkel [HT21a,HT21b] and Benoist-Wittenberg [BW] (see Section 2.3). However, the two non-nested ovals example [FJS + , Theorem 1.3(1)] has no IJT obstruction to rationality but Y (R) is disconnected; hence Y is irrational.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Via la proposition 8.1, ceci résulte des rappels sur les formes d'Albert donnés ci-dessus : l'indice de α ∈ Br(k(C)) divise 2 si et seulement si la forme f + tg est isotrope sur le corps k(C). Pour (i), voir aussi la démonstration géométrique [HT,§4,Cor. 7].…”
Section: Intersections Complètes Lisses Dans Punclassified
“…Elles impliquent que X contient une conique. Une démonstration du théorème suivant (avec la restriction X(k) = ∅) est esquissée dans [HT,Theorem 9]. Nous proposons une démonstration alternative.…”
Section: Intersections Complètes Lisses Dans Punclassified